Od rewizji do apostazji i między publicystycznością a literackością. O wierszach polskiej „odwilży” - Stankowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The text is a book review of an Wiersze polskiej „odwilży” (1953-1957) (Kielce 2010). This is the first monograph of this subject, and it has a great documentary value. The author based his well-researched study on detailed archival queries in contemporary press, magazines, and leaflets. The author compared the found texts with their authors’ published poetry books, traced the relations between content, censorship interventions in reprints, and subsequent authorial modifications, which were often aimed at universalization of a poem initially written as an urgent public statement. The author meticulously reconstructed the communicational problems of thaw poems and collections.